Analysis and Development of Bina Nusantara University’s BNPCHS School of Computer Science Competition Website Using the Laravel Framework (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this thesis is to facilitate the user to view the competition information, make the registration process and payment of the contest easily, facilitate the changing of content through the system, along with the data collection. In developing this website the methodology used is the method of collecting data through literature studies and interviews. While the design method used is the Waterfall method. The results of this thesis is a website that is implemented using a framework with a Content Management System (CMS). The conclusion of developing this website is to answer user needs for information, registration, and confirmation of competition payments